2015
DOI: 10.1638/2014-0017r1.1
|View full text |Cite
|
Sign up to set email alerts
|

VALVULOPATHY CONSISTENT WITH ENDOCARDITIS IN AN ARGENTINE BOA (BOA CONSTRICTOR OCCIDENTALIS)

Abstract: An Argentine boa (Boa constrictor occidentalis) of 5 yr 7 mo of age was presented for respiratory problems and regurgitation. Radiographs revealed evidence of cardiomegaly and pneumonia. Blood smear examination revealed the presence of intracytoplasmic inclusion bodies in peripheral lymphocytes, consistent with inclusion body disease. Cultures of a tracheal wash sample resulted in growth of Ochrobactrum intermedium and Pseudomonas putida. Echocardiographic examination revealed a large vegetative lesion on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In addition, the bacterial agents found in the present study are commonly reported as belonging to the microbiota of snakes, especially in the oral cavity and intestines [8,9]. However, under conditions of high pathogenicity, they may develop clinical manifestations in other organs [2,14], as found in this study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, the bacterial agents found in the present study are commonly reported as belonging to the microbiota of snakes, especially in the oral cavity and intestines [8,9]. However, under conditions of high pathogenicity, they may develop clinical manifestations in other organs [2,14], as found in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Reptiles are considered reservoirs of important zoonotic microorganisms, such as P. aeruginosa, which can be transmitted by fecal contact, bites and wounds [3,6,13,14]. However, the limited information available on these infections in captive reptiles indicates the need for further studies to establish their zoonotic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities have been described in snakes with IBD. In one study, a valvulopathy was detected in a boa constrictor with IBD . In other studies, neoplasia and coinfections with reovirus and adenovirus have been found associated with IBD.…”
Section: Discussionmentioning
confidence: 92%
“…belong to the microbiota of snakes, especially in their oral cavity [4,6,17]. However, in conditions of high pathogenicity, clinical manifestations and lesions can develop in their oral cavity and even in other organs [4,11,18]. In the present study, the P. aeruginosa behaved as an opportunistic pathogen, resulting in clinical manifestations with caseous lesions in the oral cavity, probably due to an imbalance of the microbiota caused by stress or immunodepression.…”
Section: Discussionmentioning
confidence: 99%